Factors affecting variations in the hydrological cycle at different temporal and spatial scales - Bonacci, Ognjen (Acta hydrotechnica, 2023)
The climate is changing intensively, causing major variations in the local, regional, and eventually global hydrological cycle. Furthermore, climate changes strongly affect individual components of the hydrological cycle. The prevailing present-day opinion is that climate change is primarily caused by anthropogenic production of CO2. This assumption is automatically accepted as the main reason or at least a contributory cause of changes in the hydrological cycle. However, changes in hydrological cycle appear to be a significantly more complex problem. At the same time, various other processes take place on different temporal and spatial scales. The article discusses numerous natural and human-caused factors that can affect changes in the hydrological cycle. When considering the factors that affect the planetary hydrological cycle on any temporal or spatial scale, it is necessary to consider many potential causes and understand their interactions. The natural factors discussed in this paper are Milanković cycles, Wolf number, Hurst phenomenon, earthquakes, volcanoes, and meteorite impacts. Among the anthropogenic influences, the role of dams and reservoirs is emphasized.
Keywords: dams; earthquakes; El Nino; hidrološki procesi; Hurst phenomenon; Hurstov pojav; hydrological processes; La Nina; Milanković cycles; Milankovićevi cikli; potresi; pregrade; reservoirs; volcanoes; vulkani; Wolf number; Wolfovo število; zadrževalniki